Sistem Informasi Penjualan dan Tabungan Hewan Qurban (Studi Kasus : DKM Masjid Baitirrahman) - Yus Jayusman; Abdurrahman Abdurrahman; Rahmat Jaenal (LPPM STMIK Bandung, 2022)
The qurban animal sales and savings information system is a website-based application designed to make it easier for people to save qurban animals so that they no longer have to bother going to the administrators but now it is easy to do anywhere and anytime, this information system provides a place for qurban animal sellers so that traders no longer keep their qurban animals to the markets but can be done online by using this information system, it is hoped that DKM administrators can provide detailed reports and do not need to wait for 1 to 3 in their presentation. Therefore, the purpose of this qurban animal sales and savings information system is to make it easier for all elements of society who want to save and sell their savings animals.